Upholding Gender Justice Principles within the Framework of Islamic Law - Din Alief Alwan Aldin; Befri Alfian; Kurniati K (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The development of gender justice discourse in contemporary Islam demonstrates a significant diversity of paradigms of thought, particularly in responding to the tension between classical fiqh normative texts and modern equality demands. This study aims to analyze the differences in the characteristics of Islamic legal thought paradigms, their critical implications for the implementation of family law, and their values in the context of maqasid al-sharia. Using a descriptive-qualitative approach with a normative-empirical literature study, the analysis is carried out through mapping textual and contextual paradigms, critical evaluation, and transformational reconstruction based on the Qur'an and Hadith. The results show a gap between the ontological principle of equality in the Qur'an and formalistic legal practices that are still influenced by patriarchal culture, where the dominance of textual approaches has not fully realized the benefit (maslahah) for women. The study recommends a paradigm synthesis for the development of applicable, inclusive, and gender-just Islamic law.